Avaliação do tempo de trânsito orocecal e do teste de tolerância à glicose em pacientes chagasicos e não chagasicos com ou sem constipação intestinal - Bafutto, Mauro (2014)
Background : Most patients with chagasic megacolon presents constipation. However in about one third of patients, despite the megacolon, bowel habits are normal.On the other hand, Chagasic patients may show constipation without evidence of colonic involvement.Thus, the determining factors of constipation in Chagas disease, are not completely understood. The question then arises: if it's not the megacolon solely responsible for constipation, what other factors are involved? In an attempt to answer this question, we evaluated the possibility of involvement not only of the colon, but also of the small intestine, very important organ in the absorption of nutrients and the formation of fecal bolus. This study evaluated whether there is change on orocecal transit and glucose absorption in the small intestine of Chagasic patients and non Chagasic with or without constipation by orocecal transit time measurement and the oral glucose tolerance test. Methods :Six groups of patients were studied: 1) – control group-Without constipation without megacolon and negative for Chagas disease serology; 2)-With constipation without megacolon and negative serology for Chagas disease; 3)-With constipation without megacolon and positive serology for Chagas disease; 4)-Without constipation without megacolon and positive serology for Chagas disease, 5)-With constipation with megacolon and positive serology for Chagas disease. 6)-Without constipationwith megacolon and positive serology for Chagas disease. For measurement of the orocecal transit time was used the H2 expired test. Results : It was observed a great extension of this time in the Group of patients with chagasic megacolon and constipation, which was statistically significant (p=0,001) when compared to all the other groups studied. It was observed that this time is greater in constipated than not constipated (p=0,005). The oral glucose tolerance test used in the evaluation of glycemic curve, showed that blood glucose levels were lower in Chagas disease patients, with statistically significant difference in relation to patients with Chagasic constipation and/or megacolon at 30 (p=0,003),60(p=0,005) e 90 minutes (p=0,001). It was interesting to note that patients with constipation and megacolon, were the only ones among all groups, which showed statistically significant difference at the same time both for the glucose tolerance test as to orocecal transit time. In conclusion, Chagasic patients with constipation and megacolon the orocecal transit time is delayed and during glucose tolerance test present highest rates of blood glucose.These data can correspond to a dysfunction of peristalsis and glucose absorption in the small intestine in patients with Chaga´s disease presenting with megacolon and constipation.